x+56=94

Simple and best practice solution for x+56=94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+56=94 equation:


Simplifying
x + 56 = 94

Reorder the terms:
56 + x = 94

Solving
56 + x = 94

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + x = 94 + -56

Combine like terms: 56 + -56 = 0
0 + x = 94 + -56
x = 94 + -56

Combine like terms: 94 + -56 = 38
x = 38

Simplifying
x = 38

See similar equations:

| 0=153-16t^2 | | -6+4+4b=-3b+9 | | y=(1+9)(1-3)(2(1)-3) | | (12y+4)-(3y+3)= | | H=153-16t^2 | | X-.1x=36 | | 20x/5x | | Y=-3/10 | | -10.9*3.4= | | 8=16.9c | | 2(11+4c)=38 | | 5x+105=180 | | 3x+2(x-6)=12 | | 7=-13+.4b | | 180-2x-6=124 | | -(((sin(x)+1)*sin(x-cos(x))-1)*sin(x+cos(x-cos(x)))-1)*cos(x-cos(x+cos(x-cos(x))))=0 | | -7=-13+.4b | | 3n+8+n=28 | | 6+13n=25780 | | 6y+2=4y+8 | | 7(x-21)=35 | | -h+9=-29 | | -(-2y+3w-8x)= | | 10(5-4y)=20 | | (2x+15)=x+15 | | f(x)=-4x^2-8x-3 | | y=(4+7)(4-4)(2(4)-3) | | y-4=15-2y | | -3(8)(8-10)-6(5-3(8))= | | f(x)=4x^2-8x-3 | | D/7=3.8 | | y=(-7+7)(-7-4)(2(-7)-3) |

Equations solver categories